2018
DOI: 10.1111/jmg.12427
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of former melt flux through high‐strain zones

Abstract: High‐strain zones are potential pathways of melt migration through the crust. However, the identification of melt‐present high‐strain deformation is commonly limited to cases where the interpreted volume of melt “frozen” within the high‐strain zone is high (>10%). In this contribution, we examine high‐strain zones in the Pembroke Granulite, an otherwise low‐strain outcrop of volcanic arc lower crust exposed in Fiordland, New Zealand. These high‐strain zones display compositional layering, flaser‐shaped mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 109 publications
(184 reference statements)
3
32
1
Order By: Relevance
“…They reported that transpression in the lower crust involved vertical and nonvertical transport of material, including small volumes of melt within mylonitic shear zones. Work in the Pembroke granulite shows evidence for extensive melt migration through the lower crust at this time and that melt-rock interaction involved little crystallization of melt within the modified rocks (Stuart et al, 2016(Stuart et al, , 2017(Stuart et al, , 2018. That work, together with our new titanite ages, demonstrates that high-strain and subsolidus deformation outlasted emplacement of the Western Fiordland Orthogneiss by 10-15 m.y.…”
Section: Transpression and Melt Mobilization In Arc Crustsupporting
confidence: 51%
See 1 more Smart Citation
“…They reported that transpression in the lower crust involved vertical and nonvertical transport of material, including small volumes of melt within mylonitic shear zones. Work in the Pembroke granulite shows evidence for extensive melt migration through the lower crust at this time and that melt-rock interaction involved little crystallization of melt within the modified rocks (Stuart et al, 2016(Stuart et al, , 2017(Stuart et al, , 2018. That work, together with our new titanite ages, demonstrates that high-strain and subsolidus deformation outlasted emplacement of the Western Fiordland Orthogneiss by 10-15 m.y.…”
Section: Transpression and Melt Mobilization In Arc Crustsupporting
confidence: 51%
“…Other workers, however, have suggested that changes in the thermal gradient of country rocks dominantly control magma transport (Vigneresse, 1995;Johnson, 2009). The interplay between pluton emplacement and transpression at different crustal levels is still poorly understood; consequently, an enhanced understanding of the way(s) in which magma is transferred and emplaced within continental arcs during periods of regional deformation can elucidate a fundamental question in the evolution of continental crust and magmatic arc systems (e.g., Paterson et al, 1998;Paterson and Schmidt, 1999;Blanquat et al, 1998;Vigneresse and Clemens, 2000;Pereira et al, 2013;Bitencourt and Nardi, 2000;Sen et al, 2014;Webber et al, 2015;Stuart et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The widespread occurrence of melt veins in a range of partially molten protoliths is the most common line of evidence (Brown, 2013; Clarke, Daczko, Klepeis, & Rushmer, 2005; Daczko, Clarke, & Klepeis, 2001; Marchildon & Brown, 2003; Sawyer, 2001, 2014; Yakymchuk et al., 2013). However, there are also abundant field examples highlighting that melt segregates into and is probably significantly transported via largely ductile shear zones (Brown, 1994, 2004, 2013; D’Lemos, Brown, & Strachan, 1992; Daczko, Piazolo, Meek, Stuart, & Elliot, 2016; Stuart, Daczko & Piazolo, 2018; Stuart, Meek, Daczko, Piazolo & Huang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Photo A was provided by Stephen Cox and is from the Wattle Gully gold mine in central Victoria, Australia (Cox, 1995). Photos B–F are from the Pembroke Granulite, Fiordland, New Zealand (Daczko, Clarke, et al, 2001; Daczko, Klepeis et al, 2001; Daczko et al., 2016; Meek, Piazolo, & Daczko, 2019; Milan, Daczko, Clarke, & Allibone, 2016, 2017; Schröter et al., 2004; Stuart Daczko & Piazolo, 2017; Stuart, Meek, Daczko, Piazolo, & Huang, 2018; Stuart Piazolo, & Daczko, 2016; Stuart, Piazolo, Piazolo, & Daczko, 2018). (a) and (b) Identical orientations of and geometric/kinematic relations between near‐coevally developed ductile foliation, brittle–ductile shear zones and veins (dykes) in extensional (tensile) fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Melting will be restricted to the areas immediately in and around these structures, as these are the only parts of the near‐ and suprasolidus orogenic crust that is diffusively accessible to H 2 O. The localized nature and spaced distribution of shear zones and recognized melt conduits (Brown, 2013; Brown & Solar, 1998a, 1998b; D'Lemos, Brown, & Strachan, 1992; Kisters et al., 2009; Reichardt & Weinberg, 2012; Rosenberg, 2004; Stuart, Piazolo, & Daczko, 2018; Weinberg, 1999) imply that the volume of crust that can potentially be affected by diffusive H 2 O‐fluxed melting is a minor portion of the anatectic orogenic crust as a whole. This ultimately limits its effectiveness as a means of generating granitic melt.…”
Section: Discussionmentioning
confidence: 99%